2019
DOI: 10.15252/embj.2018101426
|View full text |Cite
|
Sign up to set email alerts
|

C/EBPα mediates the growth inhibitory effect of progestins on breast cancer cells

Abstract: Steroid hormones are key gene regulators in breast cancer cells. While estrogens stimulate cell proliferation, progestins activate a single cell cycle followed by proliferation arrest. Here, we use biochemical and genome‐wide approaches to show that progestins achieve this effect via a functional crosstalk with C/EBPα. Using ChIP‐seq, we identify around 1,000 sites where C/EBPα binding precedes and helps binding of progesterone receptor (PR) in response to hormone. These regions exhibit epigenetic marks of act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 87 publications
(126 reference statements)
2
18
0
Order By: Relevance
“…The AR, like most nuclear receptors, binds to thousands of chromosomal sites but only regulates hundreds of genes 49,60,61 . The majority of AR-regulated gene promoters therefore physically interact with multiple ARBS 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The AR, like most nuclear receptors, binds to thousands of chromosomal sites but only regulates hundreds of genes 49,60,61 . The majority of AR-regulated gene promoters therefore physically interact with multiple ARBS 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Transcriptional regulation in early stage of lactation and in later involution process [46] Tumor suppressor [46][47][48] c/EBPβ Promotes adipogenesis. Transcription factor at pre-adipogenesis.…”
Section: Transcriptional Regulation Of Adipose Tissuementioning
confidence: 99%
“…After binding to the adipogenic enhancer sites on PPARγ and C/EBPα, it assists other adipogenic transcription factors such as the glucocorticoid receptor, STAT5A and RXR 9 to form adipogenic enhancers [49]. PPARγ and C/EBPα both play a role in the terminal differentiation of adipogenesis and are both considered tumor suppressors [45][46][47][48]95]. However, evidence suggests that PPARγ does not initiate tumor formation in normal breasts whereas in a tumor environment, the expression of PPARγ results in tumor progression signaling [45].…”
Section: Ndmentioning
confidence: 99%
“…Although administration of PR agonist MPA to mice promotes the formation of mammary tumors initiated by DMBA [31], it exerts a biphasic response in cell lines, such as a rapid proliferation burst followed by a sustained growth arrest [32][33][34]. More recently, several articles clearly showed that in addition to proliferative action, under certain circumstances, progesterone has also an anti-proliferative action in cellulo and in vivo [22,34,35]. Interestingly, although ERα-36 has no striking effect on cell growth, we found that its depletion abolished the inhibitory effect of progesterone on FBS-and E2-dependent cell proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…The p value determined by comparing each ERα-36 KO clone to the corresponding condition in WT cells using Student's t test was not significant the RNA polymerase III, regulating tRNA transcription affecting gene sets at the translational level [35]. More recently, Vicent's team showed that progesterone negatively regulates cell proliferation via a functional crosstalk with the transcription factor C/EBPα [34]. Interestingly, we found that the progesterone-induced C/EBPα expression was dependent on ERα-36.…”
Section: Discussionmentioning
confidence: 99%